2006
DOI: 10.1099/ijs.0.64029-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus aerius sp. nov., Bacillus aerophilus sp. nov., Bacillus stratosphericus sp. nov. and Bacillus altitudinis sp. nov., isolated from cryogenic tubes used for collecting air samples from high altitudes

Abstract: Four novel bacterial strains were isolated from cryogenic tubes used to collect air samples at altitudes of 24, 28 and 41 km. The four strains, 24K T , 28K T , 41KF2a T and 41KF2b T , were identified as members of the genus Bacillus. Phylogenetic analysis based on 16S rRNA gene sequences indicated that three of the strains, 24K T , 28K T and 41KF2a T , are very similar to one another (>98 % sequence similarity) and show a similarity of 98-99 % with Bacillus licheniformis and 98 % with Bacillus sonorensis. DNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
173
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(188 citation statements)
references
References 24 publications
11
173
2
2
Order By: Relevance
“…Bacteria of the Bacillus pumilus clade are ubiquitous in a wide variety of terrestrial and marine environments, ranging from stratospheric air to deep-sea sediments and from soil to living beings (Shivaji et al, 2006;Liu et al, 2013;Branquinho et al, 2014). As a consequence of a proposal recommending to invalidate two species, Bacillus aerophilus and Bacillus stratosphericus (Branquinho et al, 2015;Liu et al, 2015a), and reclassification of Bacillus invictae as a later heterotypic synonym of Bacillus altitudinis (Liu et al, 2015b), the B. pumilus clade currently comprises four species with validly published names, B. pumilus, Bacillus safensis (Satomi et al, 2006), B. altitudinis (Shivaji et al, 2006) and Bacillus xiamenensis (Lai et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria of the Bacillus pumilus clade are ubiquitous in a wide variety of terrestrial and marine environments, ranging from stratospheric air to deep-sea sediments and from soil to living beings (Shivaji et al, 2006;Liu et al, 2013;Branquinho et al, 2014). As a consequence of a proposal recommending to invalidate two species, Bacillus aerophilus and Bacillus stratosphericus (Branquinho et al, 2015;Liu et al, 2015a), and reclassification of Bacillus invictae as a later heterotypic synonym of Bacillus altitudinis (Liu et al, 2015b), the B. pumilus clade currently comprises four species with validly published names, B. pumilus, Bacillus safensis (Satomi et al, 2006), B. altitudinis (Shivaji et al, 2006) and Bacillus xiamenensis (Lai et al, 2014).…”
mentioning
confidence: 99%
“…As a consequence of a proposal recommending to invalidate two species, Bacillus aerophilus and Bacillus stratosphericus (Branquinho et al, 2015;Liu et al, 2015a), and reclassification of Bacillus invictae as a later heterotypic synonym of Bacillus altitudinis (Liu et al, 2015b), the B. pumilus clade currently comprises four species with validly published names, B. pumilus, Bacillus safensis (Satomi et al, 2006), B. altitudinis (Shivaji et al, 2006) and Bacillus xiamenensis (Lai et al, 2014). In a preliminary investigation of the phylogenetic diversity and marine ecotype of the B. pumilus clade using multilocus sequence analysis (Liu et al, 2013), strains DW5-4 T and NH7I_1 T were found to form two independent clades which were marked group C and group E, respectively.…”
mentioning
confidence: 99%
“…The ubiquitous distribution of Bacillus species in nature is due to the resistance of their endospores to chemical and physical agents. Species of Bacillus have been shown to be resistant to radiation (Shivaji et al, 2006;Venkateswaran et al, 2003), extremely low temperatures (Brambilla et al, 2001;Logan et al, 2000;Rüger et al, 2000;Nelson & Parkinson, 1978;Abd El-Rahman et al, 2002;Lechner et al, 1998), high temperatures (Baker et al, 2001;Caccamo et al, 2000;Combet-Blanc et al, 1995), salinity Lee et al, 2006;Gugliandolo et al, 2003), alkalinity (Nogi et al, 2005;Vargas et al, 2005;Yumoto et al, 1998), acidity (Albert et al, 2005) and high pressure (Bae et al, 2005). Although Bacillus species have been isolated from a wide range of habitats, only one Bacillus species with a validly published name, Bacillus lehensis (Ghosh et al, 2007), has been isolated from the Himalayan region.…”
mentioning
confidence: 99%
“…Growth occurs between 8 and 45°C at pH 5-8. It tolerates up to 2% NaCl and degrades tyrosine, but tests negative for casein hydrolysis, urease, and phenylalanine deaminase activities, reduction of nitrate to nitrite, utilization of citrate and the Voges-Proskauer test [3].…”
Section: Bacteriamentioning
confidence: 99%